Community of Ephilitic peryphiton in the Kampar River, Tabing Village, XIII Koto Kampar District, Riau Province - Umi Asni; Adriman '; Nur El Fajri (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Peryphiton has an important role in food chain, as it is able to absorb CO2 and release O2 which is very useful for other organisms and environment. The purpose of this research is to study the community which includes the abundance, diversity and the type of dominant ephilitic peryphiton in the Kampar River that flown in the Tabing Village. This research was conducted in January 2015. Peryphiton samples were collected from 4 stations. The peryphiton was collected by scraping stone surface (5 x 5 cm) using a tooth brush. The scraped materials were kept in plastic jars and filled with 50 ml aquadest and then were fixed using lugol (3 drops/ 50 ml samples). The peryphiton were then identified based on YunFang (1995). Results shown that there were 49 species of ephilitic peryphiton and they were belonged to 5 classes, namely Bacillariophyceae, Chlorophyceae, Cyanophyceae, Xanthophyceae and Dinophyceae. The abundance of the peryphiton ranged from 9,833 – 32,917 cells/l and the diversity index (H ') ranged from 3.995 - 4.928, it means that the distribution of each type is high. The uniformity (E) index ranged from 0.871 - 0.988, it means that the uniformity is balance. The Dominancy index (C) ranged from 0.043 - 0.269, it means that there is no dominant species. These results demonstrate that the diversity of the ephilitic peryphiton in the Kampar River is high and there is no dominant species.Keywords: Community, periphyton Epilitik, Kampar River